Pornography and sex crimes in the Czech Republic - Diamond, Milton; Jozifkova, Eva; Weiss, Petr (Archives of sexual behavior, 2011)
Pornography continues to be a contentious matter with those on the one side arguing it detrimental to society while others argue it is pleasurable to many and a feature of free speech. The advent of the Internet with the ready availability of sexually explicit materials thereon particularly has seemed to raise questions of its influence. Following the effects of a new law in the Czech Republic that allowed pornography to a society previously having forbidden it allowed us to monitor the change in sex related crime that followed the change. As found in all other countries in which the phenomenon has been studied, rape and other sex crimes did not increase. Of particular note is that this country, like Denmark and Japan, had a prolonged interval during which possession of child pornography was not illegal and, like those other countries, showed a significant decrease in the incidence of child sex abuse.
Keywords: dospělí; Public Opinion; Crime; Female; dítě; Adult; právní vědy; Erotica; ženské pohlaví; Attitude to Health; lidé; postoj ke zdraví; Sexual Behavior; sexuální delikty; sexuální chování; Male; Czech Republic; Social Perception; Internet; veřejné mínění; Jurisprudence; Česká republika; Child; Mass Media; mužské pohlaví; zločin; sociální percepce; internet; hromadné sdělovací prostředky; Sex Offenses; erotika; Humans